Hypoxia and Human Genome Stability: Downregulation of BRCA2 Expression in Breast Cancer Cell Lines. (19th September 2013) - Fanale, Daniele; Bazan, Viviana; Caruso, Stefano; Castiglia, Marta; Bronte, Giuseppe; Rolfo, Christian; Cicero, Giuseppe; Russo, Antonio
Abstract : Previously, it has been reported that hypoxia causes increased mutagenesis and alteration in DNA repair mechanisms. In 2005, an interesting study showed that hypoxia-induced decreases in BRCA1 expression and the consequent suppression of homologous recombination may lead to genetic instability. However, nothing is yet known about the involvement of BRCA2 in hypoxic conditions in breast cancer. Initially, a cell proliferation assay allowed us to hypothesize that hypoxia could negatively regulate the breast cancer cell growth in short term in vitro studies. Subsequently, we analyzed gene expression in breast cancer cell lines exposed to hypoxic condition by microarray analysis. Interestingly, genes involved in DNA damage repair pathways such as mismatch repair, nucleotide excision repair, nonhomologous end-joining and homologous recombination repair were downregulated. In particular, we focused on the BRCA2 downregulation which was confirmed at mRNA and protein level. In addition, breast cancer cells were treated with dimethyloxalylglycine (DMOG), a cell-permeable inhibitor of both proline and asparaginyl hydroxylases able to induce HIF-1 α stabilization in normoxia, providing results comparable to those previously described. These findings may provide new insights into the mechanisms underlying genetic instability mediated by hypoxia and BRCA involvement in sporadic breast cancers.